Frequentare l’Università, tra dovere e diritto allo studio - Farinelli, Giovanna (Studi sulla Formazione/Open Journal of Education, 2024)
The university as a place of personal, relational and organizational well-being implies the recognition of the need for attendance and participation not only as a right to study but above all as a duty, as stated in the second paragraph of article 4 of the Italian Constitution: “Every citizen shall have the duty, according to personal potential and individual choice, to perform any activity or function contributing to the material or spiritual progress of society”. The current legislation guarantees transparency and trust in the university as a public institution through the arrangement of times and spaces of the teacher-student educational relationship. This implies active participation, daily contact and discussion; the university represents a community in a territory; it is a "free space" for discussion, a “gym” in person, without excluding the telematic mode. As at the origin, it is necessary to consider the university not as a place of domination and control of knowledge for a hypocritical plurality of knowledge caged by scientific disciplinary sectors, but as an interdisciplinary environment for a “participatory knowledge”: an authentic and effective osmosis between the academic community and civil society. This reaffirms the moral duty of attendance and participation against a hypocritical, immoral and illegal “exemption from attendance”, commonly defined as “non-obligation to attend”. Participation is the essence not only of academic life but of life itself.